Radial thermal expansion of pure and Xe-saturated bundles of single-walled carbon nanotubes at low temperatures - Dolbin, A.V.; Esel`son, V.B.; Gavrilko, V.G.; Manzhelii, V.G.; Popov, S.N.; Vinnikov, N.A.; Danilenko, N.I.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The radial thermal expansion coefficient ar of pure and Xe-saturated bundles of single-walled carbon nanotubes (CNT) has been measured in the interval 2.2-120 K. The coefficient is positive above T = 5.5 K and negative at lower temperatures. The experiment was made using a low-temperature capacitance dilatometer with a sensitivity of 2·10-9 cm and the sample was prepared by compacting a CNT powder such that the pressure applied oriented the nanotube axes perpendicular to the axis of the cylindrical sample. The data show that individual nanotubes have a negative thermal expansion while the solid compacted material has a positive expansion coefficient due to expansion of the intertube volume in the bundles. Doping the nanotubes with Xe caused a sharp increase in the magnitude of ar in the whole range of temperatures used, and a peak in the dependence ar(T) in the interval 50-65 K. A subsequent decrease in the Xe concentration lowered the peak considerably but had little effect on the thermal expansion coefficient of the sample outside the region of the peak. The features revealed have been explained qualitatively.